Oncological outcome and prognostic factors of surgery for soft tissue sarcoma after neoadjuvant or adjuvant radiation therapy: A retrospective analysis over 15 years - Muehlhofer, Heinrich M. L.; Schlossmacher, Benjamin; Lenze, Ulrich; Lenze, Florian; Burgkart, Rainer; Gersing, Alexandra S.; Peeken, Jan C.; Combs, Stephanie E.; Von Eisenhart-Rothe, Ruediger; Knebel, Carolin (Anticancer Research, 2021)
Background/Aim: Surgical resection for soft tissue sarcomas (STSs) is the gold standard for a curative oncologic therapy in combination with neoadjuvant or adjuvant radiation therapy (NRT/ART). The aim of this study was to determine prognostic factors influencing the survival of patients with STS undergoing NRT or ART considering various parameters in a retrospective, single-centre analysis over 15 years. Patients and Methods: We included 119 patients (male 59) and the median follow-up period was 69 months (4-197). The patients received NRT (n=64) or ART (n=55). We recorded the histopathologic subtype of STS, tumour grade, localization, tumour margins, complications, survival, local recurrence, and metastases. Survival analysis was performed using the Kaplan-Meier method. Results: The overall survival rate was 68.9% at 5 years. The localization (epifascial/subfascial), resection margin and type of radiation therapy (NRT/ART) had no significant impact on survival. Tumour grade, tumour size, local recurrence and metastases were significantly correlated with patient survival (p<0.05). Local recurrence was significantly higher in patients with ART (p=0.044). Conclusion: Tumour grade and tumour size were independently associated with diseasespecific survival, and patients with local recurrence and metastases had lower survival rates.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Prognostic factors; Radiation therapy; Soft tissue sarcoma; Surgery